2019
DOI: 10.2196/13062
|View full text |Cite
|
Sign up to set email alerts
|

Publicly Funded Home and Community-Based Care for Children With Medical Complexity: Protocol for the Analysis of Medicaid Waiver Applications

Abstract: Background Children with medical complexity are a group of children with multiple chronic conditions and functional limitations that represent the highest health care utilization and often require a substantial number of home and community-based services (HCBS). In many states, HCBS are offered to target populations through 1915(c) Medicaid waivers. To date, no standard methods or approaches have been established to evaluate or compare 1915(c) waivers across states in the United States for childre… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 29 publications
0
9
0
Order By: Relevance
“…As such, many families either go without accessing these services or attempt to provide the services themselves which leads to increase financial and psychological burdens on the entire family (Thomson et al, 2016 ). Beyond the difficulty experienced by families attempting to navigate the complicated HCBS terrain, we have found that pediatric providers are also left with similar feelings of confusion and frustration (Keim‐Malpass, Constantoulakis, et al, 2019 ; Keim‐Malpass, Letzkus, et al, 2019 ).…”
Section: Introductionmentioning
confidence: 89%
See 4 more Smart Citations
“…As such, many families either go without accessing these services or attempt to provide the services themselves which leads to increase financial and psychological burdens on the entire family (Thomson et al, 2016 ). Beyond the difficulty experienced by families attempting to navigate the complicated HCBS terrain, we have found that pediatric providers are also left with similar feelings of confusion and frustration (Keim‐Malpass, Constantoulakis, et al, 2019 ; Keim‐Malpass, Letzkus, et al, 2019 ).…”
Section: Introductionmentioning
confidence: 89%
“…Relevant waivers were included if: they were nonexpired from December 31, 2017, to October 31, 2018, and included children (ages 0–21) in their eligibility. As part of the larger parent study, the authors developed a systematic search and data extraction template to abstract key elements from the Medicaid applications (Keim‐Malpass, Constantoulakis, et al, 2019 ; Keim‐Malpass, Letzkus, et al, 2019 ). A systematic extraction template was used to classify the elements included in the waivers, including dollars allocated per individual, time an individual can remain on the waiver, use of cost containment strategies (capitation or individual cost limits), the possibility that a child could transition as an adult within the same waiver without a reapplication, range of pediatric ages covered, and the scope of the service type allowed on the waiver (Keim‐Malpass, Constantoulakis, et al, 2019 ; Keim‐Malpass, Letzkus, et al, 2019 ).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations